Coastal Issues and Management Strategy for Sagar Island in Bay of Bengal - and J.K. Patterson Edward, S. Asta Lakshmi* (Recent Research in Science and Technology, 2010)
Sagar Island, situated in the east coast of India is one of the biggest deltaic Islands in Sundarban group. This Island is unique with its natural ecosystem and has a potential for becoming a prime eco-tourism destination. The natural and man-made problems affect the quality of environment and life of people in Sagar Island. This paper examines the severe coastal issues of Sagar Island that include coastal erosion, threat to biodiversity, natural hazards, tourism and livelihood insecurity of local communities.Â It recommends adoption of a management strategy by implementing the Integrated Coastal Zone Management (ICZM) in order to mitigate these coastal issues and to ensure sustainable development of the coastal environment of Sagar Island in Sundarban Biosphere Reserve.